2002
DOI: 10.1111/j.1574-695x.2002.tb00567.x
|View full text |Cite
|
Sign up to set email alerts
|

Type 1, P and S fimbriae, and afimbrial adhesin I are not essential for uropathogenicEscherichia colito adhere to and invade bladder epithelial cells

Abstract: Fimbrial (type 1, P, and S) and afimbrial adhesins, the unique virulence traits of uropathogenic Escherichia coli (UPEC), are well recognized for their role in the initial step of uropathogenesis. In this study, we investigated whether these adhesins are dispensable for UPEC in adherence and invasion of uroepithelial cells by using E. coli isolates (n=40) from cystitis patients and T-24 cells, the bladder carcinoma cell line. We found all isolates adherent to T-24 cells within 15 min of infection. In invasion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 25 publications
(28 reference statements)
1
8
0
Order By: Relevance
“…5). It should be also noted that the absence of fimG/H, papG or sfa did not definitely limit the biofilm formation of the studied E. coli strains, which is consist with the results presented by Miyazaki (2002). Therefore, the presence of others genes encoding adhesins is highly possible.…”
Section: Presence Of Genes Associated With Biofilm Formationsupporting
confidence: 80%
“…5). It should be also noted that the absence of fimG/H, papG or sfa did not definitely limit the biofilm formation of the studied E. coli strains, which is consist with the results presented by Miyazaki (2002). Therefore, the presence of others genes encoding adhesins is highly possible.…”
Section: Presence Of Genes Associated With Biofilm Formationsupporting
confidence: 80%
“…The ExPEC prototype strains CFT073, 536, J96, and RS218 belong to phylogroup B2, and all showed the phenotypic capacity to adhere to and invade a variety of epithelial cells, survival the complement bactericidal activity, and produce biofilms [18][19][20][21][22][23][24][25]. Nevertheless, these features were expressed at different levels in clinical isolates [22,26,27]. Moreover, most of the information related to virulence properties expression assessed in vitro were derived from strains from phylogroups B2 and D [12,24].…”
Section: Introductionmentioning
confidence: 99%
“…Type I pili are found in uropathogenic as well as human commensal E. coli strains (Levine et al, 1980). UPEC adheres even without the expression of either of these two pili, suggesting that an alternative mechanism is involved in adhesion (Miyazaki et al, 2002). Recent studies have shown the importance of yad genes in adherence, as the deletion of yad genes increases cell motility.…”
Section: Introductionmentioning
confidence: 99%